EFEKTIVITAS PENGGUNAAN E-MODUL BERBASIS POE (PREDICT, OBSERVE, EXPLAIN) TERHADAP KEMAMPUAN BERPIKIR KRITIS (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
Based on the results of observations and interviews at SMAN 5 Palangka Raya, physics learning is still not structured optimally to achieve students' critical thinking skills. As a result, research was undertaken employing POE-based e-modules to aid students in achieving learning competencies by utilizing their critical thinking skills. The goal of this study is to see how successful POE-based e-modules are at improving critical thinking skills. A quantitative approach using a One Group Pretest-Posttest Design was applied. A test in the form of a description question served as the data gathering strategy. The findings revealed that this POE-based e-module was beneficial to students' critical thinking abilities. The e-effectiveness module's was determined using an effect size of 3.24, which falls into the very high category. This study's conclusion is this POE-based e-module improves students' critical thinking skills.